Online Contract Drafting Assistance For Small Medium Enterprise In The Gentan Raya, Baki, Sukoharjo Markets - Rina Arum Prastyanti; Faulinda Elynastiti (Veteran Society : Jurnal Pengabdian Masyarakat, 2020)
The backgrounds of business actors in Pasar Raya Gentan are different. The majority of business actorshave received the highest education from high school. The educational background of this business actorinfluences one's mindset and attitude in making decisions and facing problems. The lack of educationresulted in a lack of knowledge of the significance of the Covenant. Business actors in the gentan marketoften use oral agreements that unconsciously lead to agreements. Preparation of Training Materials, Atthis stage, the team first makes a good and correct guidebook for writing agreements. Presentation ofContract Drafting and Review Business Contract Material, At this meeting the presenters providedsocialization and understanding of the importance of contract drafting. In addition, participants were alsogiven knowledge about the law of making contracts in business. Design (Skill Session), at this stage,participants are stimulated independently to be able to make a work agreement project which will laterbe applied in their field of work, Monitoring and Evaluation, after being deemed sufficient to master andunderstand the “Contract Drafting and Review Business Contract”, it is followed by monitoring andevaluating the success rate of contracting for participants, whether it has helped participants inimplementing this training. The solution offered to partners is to provide assistance in contract design forbusiness actors in Raya Gentan market. Contract drafting is an important element in a legal relationship.Contract drafting is a combination of two words, namely "contract" and "drafting". Literally, the word"contract" means promise, while "drafting" means designing / drafting. So contract drafting can beinterpreted briefly as the design of an agreement. A complete understanding of contract drafting is veryimportant for business actors